The Effect of Motivational General Arousal Imagery Training on the Mental Toughness of Handball Athletes - Tsurayya Nabillah Zahra; Nida’ul Hidayah; Mochamad Yamin Saputra (Universitas Negeri Semarang, 2025)
An athlete’s performance depends not only on physical ability and technique, but also on mental strength, which is fundamental in coping with the pressures of competition. In team sports such as handball, mental toughness greatly influences individual and team performance. One psychological method that can be used to improve mental readiness is motivational general arousal imagery, which is an imagination exercise that focuses on increasing motivation, controlling emotions, and preparing to face competitive pressure. This study aims to determine the effect of motivational general arousal imagery training on improving the mental toughness of handball athletes. The method used was a quasi-experiment with a one-group pre-test post-test design. The research sample consisted of 14 handball athletes from Bandung. The treatment was given for 12 sessions with a frequency of 3 times per week, each lasting 20-30 minutes. Mental toughness was measured using the Sport Mental Toughness Questionnaire (SMTQ) before and after the treatment. The results showed that Motivational General Arousal Imagery training had a significant effect on increasing the mental toughness of handball athletes. Based on the Wilcoxon test results with a sig. value of 0.001 < 0.05, there was a significant difference between the pre-test and post-test. The average mental toughness score increased from 27.93 to 46.93 after the treatment, indicating a significant increase in mental toughness. Motivational General Arousal Imagery training proved to be effective in increasing the mental toughness of handball athletes. Coaches and sports practitioners are advised to integrate Motivational General Arousal Imagery training into routine training. This exercise can be done simply, either individually or in groups, to improve athletes’ mental toughness.